(untitled) (American Journal of Business Management, Economics and Banking, 2024)
In this article, the teaching of economic sciences in general secondary schools will be raised to a new level, the opportunities for providing quality education, the formation of economic and entrepreneurial knowledge skills of schoolchildren, new innovative methods during the lesson will be discussed. methods of using educational methods and recommendations are given.